Modeling Teacher's Integrity Using Data Mining - Mohd Latifi, Abdul Ghani (2010)
Integrity is a concept of consistency of actions, values, methods, measures, principles, expectations and outcomes. In school, integrity is an important criterion for teachers. With high integrity characteristic, the teachers will enable to manage class excellently, encourage students in teaching and learning activities and able to complete task given by administrator on time. However there are reports that some teachers unable to perform their tasks in classroom efficiently. Researcher indicated there are many factors can affect teacher's integrity. Thus, the aim of this study is to develop a model for teacher's integrity using data mining technique. To obtain this, a dataset from a survey conducted by Pejabat Pelajaran Daerah Langkawi is taken as case study for the model construction. The dataset called teachers's integrity dataset contain 1500 records elaborates with 25 attributes including a target class were pre-processed and then mined using directed association rule mining algorithm namely Apriori. The mining result shows that out of 25 characteristics, only 8 influence the teacher's integrity which leads to the construction of the teacher's integrity model. The teachers must follow the rules and procedures, Understand the consequence, not use the facilities for personal purposes, never manipulate organization's information, never make false statement, honest in promotion, open to receive admonition and advice and accept anyone to be head of department are the factors that can influence teacher's integrity. Then, a prototype for classifying teacher's integrity was developed based on the model. This finding can be a guideline for the Pejabat Palajaran Daerah Langkawi to plan strategies for next generation teachers.